Investigating the Greek general government accounting reform: The challenging task of staff training - Michalis Bekiaris; Thekla Paraponti; Foteini Spanou (Contabilitate şi Informatică de Gestiune)
Purpose – This article explores the status of public sector accounting education in Greece and assesses the readiness of the Greek general government financial employees to implement accrual accounting. Design/methodology/approach – Using a mixed-research design combining online research with quantitative and qualitative analysis, we record the available public sector accounting vocational programs and assess the financial employees’ educational level and training status. Findings – The online research and quantitative analysis findings suggest limited availability of suitable vocational training programs and a low level of readiness to implement IPSAS-based accrual accounting in the Greek public sector. The qualitative analysis indicates the need to design specialized vocational programs that address the needs and specificities of different government sub-sectors. Originality – The study is the first to analyze the educational adequacy and availability of vocational programs in Greece and assess the educational and professional competence of Greek general government financial employees vis-à-vis the requirements of the ongoing accrual accounting reform.